Cyklofotokoagulacja laserem diodowym – ocena skuteczności w obniżaniu ciśnienia wewnątrzgałkowego w porównaniu z cyklodiatermią pod płatkiem - Szaflik, Jerzy; Zawadzka, Danuta; Zaleska-Żmijewska, Anna (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
The aim of this study was to retrospectively analyze intraocular pressure and state of the eyeball in patients treated with diode laser, and to compare the outcomes with a group of patients after cyclodiatermy under the scleral flap. We analyzed: visual acuity, IOP, percentage of lowering the IOP from the beginning, subjective patients' feelings of pain and complications. Conclusions: TSCPC is safe for patients and may be repeated, if needed. Laser cyclodestruction gives new possibilities in noninvasive IOP lowering with less complications than cyclodiatermy, without changes in patient's visual functions.